cience and Charity, Educational therapy and active learning, increasing brain intelligence or heart intelligence - Aan Eko Khusni Ubaidillah (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2019)
Transhumanism, a unique cyber entity perspective, posthumanism offers a unique integration between agency, memory and imagination in a philosophical way to achieve a harmonious ecology harmony that is developing and interrelated, increasing the education provided to graduates is necessary. The purpose of this paper discusses learning of Science and Charity, how education therapy and active learning, as well as improving brain intelligence or heart intelligence. From the results of the discussion it was concluded: 1) Various studies related to the phenomenon of the era of education 4.0 in general need to improve the education given to graduates therefore if society changes, schools need to change preparing students for the real world, rather than instead isolating students from the real world because students need to be a critical thinker and ready to solve problems, collaborate and communicate; 2) Education must teach the renewal of capacity to create, identify issues regarding current situations and actively provide solutions through the integration of faith, knowledge, charity or creed, shari'ah, morals; 3) Education must provide an ideal mode of therapy Lecture, Reading, Audiovisual, Demonstration, Discussion, Practice and Real Practice with a percentage ratio of 5: 10: 20: 30: 50: 75: 90, or use other patterns and not 100% lecture; 4) educational elements and principals must understand the concepts of knowledge for practice and knowledge in practice which consists of different varieties of knowledge as competitors or complementary such as formal knowledge (referring to theory or research and law or policy) and informal (referring to the practice of wisdom, experience personal, intuitive and tacit knowledge); 5) Other countries are fast advancing on the basis of creativity and innovation as the drivers of the knowledge economy by shifting the education system with the core of considering the abilities and talents of individuals and to create new knowledge.